Monitoring and Prediction of Blast Vibrations : A Case Study - D Vidyarthi (International Society of Explosives Engineers, 2007)
Blasting is the most important activity in the mining industry, the world over. It is a well known fact that only part of the explosive energy gets utilized in causing the actual rock fragmentation. The rest of it gets converted into blast-induced ground vibrations and noise. Though blast vibrations cannot be totally eliminated, it is possible to minimize them by optimization of blast parameters. This paper highlights various in-house efforts put forth by the author towards site specific blast optimization and the monitoring of blast vibrations. It also deals with the prediction curves developed by regular regression analysis for the prediction of ‘blast vibrations’, ‘peak particle velocity’, ‘safe charge’ for various blasts.